40 Gb/s Mode-Division Multiplexed DD-OFDM Transmission Over Standard Multi-Mode Fiber - Jiawei Luo; Jianping Li; Qi Sui; Zhaohui Li; Chao Lu (IEEE Photonics Journal, 2016)
A 40 Gb/s mode-division multiplexed (MDM) direct detection optical frequency-division multiplexing signal transmission over standard multimode OM3 fiber (MMF) has been demonstrated in this paper. Error-free unidirectional and bidirectional transmissions over 200-m standard MMF under the forward error control (FEC)-limit can be realized. Advanced digital signal processing algorithms based on directed-detection techniques using single photodiodes have also been studied to eliminate the crosstalk and improve the performance of MDM systems.